Examination of the shoulder the complete guide - McFarland, Edward G. (Thieme, 2006)
Written to provide full understanding of shoulder anatomy and the principles of physical shoulder examination and the nature and presentation of the pathological processes causing shoulder pain, this text discusses range of motion measurements, laxity testing, shoulder instability and presents critical analysis of the usefulness and accuracy of examination practices.